Halotolerant Phosphat Solubilizing Bacteria from Paddy Saline Soil - Purwanto, Purwanto; Susanti, Retna; Amalia, Dwi Ayu Lutfiana; Leana, Ni Wayan Anik; Oktaviani, Eka; Kurniawan, Ruly Eko Kusuma; Omer, Omer Ahmed Mohamed; Eka Oktaviani (Universitas Negeri Semarang, 2025)
Salinity stress on productive rice fields in coastal areas will have a negative impact on productivity through osmotic stress and nutrient deficiencies. Salinity stress causes high levels of Na and Cl in the soil, thus inhibiting phosphate absorption. Utilization of indigenous P-solubilizing bacteria from saline land is an alternative, environmentally friendly technology. The purpose of this study was to isolate and characterize P-solubilizing bacteria from saline rice fields. Soil samples were taken from the rice rhizosphere in Nyamplungsari Village, Peraturkan District, Pemalang Regency. Isolation and characterization were carried out at the Agronomy & Horticulture Laboratory, Faculty of Agriculture, UNSOED. The variables observed included P solubility index, P solubilizing ability, IAA production, and bacterial identification using the 16S RNA method. The results of the study obtained 7 isolates of P-solubilizing bacteria that had the ability to solubilize P and produce IAA. Isolate KF is a P-solubilizing bacterium that has the highest P-solubilizing ability and is identified as Priestia megaterium strain NRRL B-350. Priestia megaterium strain NRRL B-350 is a species of P-solubilizing bacteria that has the potential to be developed as a specific biological fertilizer for saline soil to increase the growth and yield of rice plants under saline stress.